The First Report of Downy Mildew Caused by Peronospora belbahrii on Sweet Basil in Greenhouses in the Czech Republic - Šafránková, I; Holková, L (Plant disease, 2014)
Sweet basil (Ocimum basilicum L.) is an aromatic plant that is cultivated as a pot plant in greenhouses or in fields in the Czech Republic. The plants are intended for direct consumption or for drying. In April of 2012, the first large chlorotic from the middle necrotic spots occurred gradually on leaves of pot plants O. basilicum cv. Genovese in greenhouses in Central Bohemia. The characteristic gray to brown furry growth of downy mildew appeared on abaxial surfaces of leaves in the place of chlorotic spots within 3 to 4 days. The infested leaves fell off in the late stages of pathogenesis. The infestation gradually manifested itself in ever-younger plants and in July, cotyledons and possibly the first true leaves were already heavily infected and damaged and these plants rapidly died. The plant damage reached 80 to 100%, so it was necessary to stop growing the plants in the greenhouse at the end of July. The causal agent was isolated and identified as Peronospora belbahrii Thines by means of morphological and molecular characters (2,3). Conidiophores were hyaline, straight, monopodial, 280 to 460 μm, branched three to five times, ended with two slightly curved branchlets with a single conidia on each branchled tip. The longer branchlets measured 13 to 24 μm (average 18.2 μm), the shorter one 4 to 15 μm (average 9.7 μm). Conidia were rounded or slightly ovoid, from brownish to dark brownish, measured 22 to 31 × 20 to 28 μm (length/width ratio 1.2). A pathogen-specific sequence was detected with the help of the pathogen ITS rDNA specific primers in symptomatic leaves (1). DNA from plant tissues was isolated using the DNeasy plant Mini Kit (Qiagen, Germany) following the standard protocol. PCR was performed using KAPA2G Robust HotStar kit (Kapa Biosystems, United States) according to the conditions recommended in Belbahri et al. (1). The specific products were visualized by electrophoresis through 1.5% agarose gels. Leaves of 20-day-old potted plants O. basilicum 'Genovese' were inoculated by spraying with 5 × 105 conidia/ml of the pathogen. Each pot contained 10 plants. Sterilized distilled water was applied to control plants. Plants were covered with polyethylene bags during the entire incubation period to maintain high humidity, and kept at a temperature of 22 to 24°C. Typical disease symptoms appeared on leaves 5 to 9 days after inoculation. Control plants were symptomless. P. belbahrii was re-isolated from the lesions of inoculated plants, thus fulfilling Koch's postulates. Downy mildew on sweet basil was reported in countries in Africa, Europe, and South and North America (4). To our knowledge, this is the first report of downy mildew on sweet basil in the Czech Republic. References: (1) L. Belbahri et al. Mycol. Res. 109:1276, 2005. (2) Y.-J. Choi et al. Mycol. Res. 113:1340, 2009. (3) M. Thines et al. Mycol. Res. 113:532, 2009. (4) C. A. Wyenandt et al. HortScience 45:1416, 2010.